2017
DOI: 10.3389/fsurg.2017.00045
|View full text |Cite
|
Sign up to set email alerts
|

Late Sac Rupture due to a Type IV Endoleak after Previous Endovascular Aortic Aneurysm Repair: A Case Report

Abstract: Type IV endoleaks have been identified as endoleaks of low flow, and rupture risk has been estimated to be minimal in literature. Therefore, conservative treatment has been recommended in most cases. We are presenting a rare case of late rupture due to type IV endoleak that was treated with open repair applying a novel surgical technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
0
0
2
Order By: Relevance
“…CT findings showed that the leakage site was close to the neck site, making it difficult to completely deny Type I because the neck was angulated and the endoleak was massive. A Type IV endoleak is usually observed without apparent contrast extravasation [ 8 , 9 ]. In the present case, the use of Viewtify and the stereoscopic display resulted in very clear 3DCG visualization.…”
Section: Discussionmentioning
confidence: 99%
“…CT findings showed that the leakage site was close to the neck site, making it difficult to completely deny Type I because the neck was angulated and the endoleak was massive. A Type IV endoleak is usually observed without apparent contrast extravasation [ 8 , 9 ]. In the present case, the use of Viewtify and the stereoscopic display resulted in very clear 3DCG visualization.…”
Section: Discussionmentioning
confidence: 99%
“…Nachdem Typ-IV-Endoleaks in der überwältigenden Mehrzahl der Fälle selbstlimitierend sind, stellt sich üblicherweise keine spezifische Behandlungsindikation [ 21 , 51 ]. Allerdings kann im Fall einer akuten Aortenruptur der persistierende Volumenverlust durch ein Typ-IV-Endoleak die hämodynamische Stabilität des Patienten signifikant beinträchtigen.…”
Section: Prävention Und Therapieunclassified
“…[21, 51]. Allerdings kann im Fall einer akuten Aortenruptur der persistierende Volumenverlust durch ein Typ-IV-Endoleak die hämodynamische Stabilität des Patienten signifikant beinträchtigen.…”
unclassified
“…Compared to T3EL, the stent graft in T4EL is intact. Chronic wear, deformation of the stent graft, and chronic exposure to the pulsatile forces might be possible mechanisms for T4EL 180 . 0.4-3% of patients developed T4EL after the aneurysm repair 147,151 , and it is far less frequent with the current generation of stent grafts.…”
Section: Type IV Endoleak (T4el)mentioning
confidence: 99%